Inhibition of Mitochondrial Aconitase by Succination in Fumarate Hydratase Deficiency - Ternette, N; Fischer, R; Kessler, B; Yang, M; Laroyia, M; O'Flaherty, L; Wolhulter, K; Adam, J; Pollard, P; Lappin, T; Kitagawa, M; Igarashi, K; et al. (2013)
The gene encoding the Krebs cycle enzyme fumarate hydratase (FH) is mutated in hereditary leiomyomatosis and renal cell cancer (HLRCC). Loss of FH activity causes accumulation of intracellular fumarate, which can directly modify cysteine residues to form 2-succinocysteine through succination. We undertook a proteomic-based screen in cells and renal cysts from Fh1 (murine FH)-deficient mice and identified 94 protein succination targets. Notably, we identified the succination of three cysteine residues in mitochondrial Aconitase2 (ACO2) crucial for iron-sulfur cluster binding. We show that fumarate exerts a dose-dependent inhibition of ACO2 activity, which correlates with increased succination as determined by mass spectrometry, possibly by interfering with iron chelation. Importantly, we show that aconitase activity is impaired in FH-deficient cells. Our data provide evidence that succination, resulting from FH deficiency, targets and potentially alters the function of multiple proteins and may contribute to the dysregulated metabolism observed in HLRCC.